Phylogenetic analysis of a 2024 Sheeppox virus isolate from the Almaty region of Kazakhstan and investigation of its pathogenicity in merino sheep - Azanbekova, Moldir; Mambetaliyev, Muratbay; Valiyeva, Aisulu; Kozhabergenov, Nurlan; Aldayarov, Nurbek; Kilibayev, Sanat; Usserbayev, Bekbolat; Tuyskanova, Moldir; Kadyrova, Balziya; Myrzakhmetova, Balzhan; Kutumbetov, Lespek; Chervyakova, Olga; et al. (Frontiers in Veterinary Science, 2025)
IntroductionSheeppox virus (SPPV) is a significant pathogen that affects small ruminants and causes substantial economic losses. It is essential to perform detailed molecular and pathogenic characterization of field isolates to control the disease and develop prevention strategies.MethodsThe SPPV isolate “Sheeppox/KZ/Targap/2024” was obtained in 2024 from a diseased lamb during an outbreak in Targap village in the Almaty region of Kazakhstan. The isolate was passaged three times in lamb kidney-cell culture, and the 50% tissue culture infectious dose (TCID50) assay indicated a titer of 5.33 ± 0.08 log10 TCID50/mL. Identification was performed using polymerase chain reaction (PCR) and whole-genome sequencing, and the complete genome was submitted to GenBank (accession number PV434148). Experimental infection studies were conducted with Merino sheep.ResultsThe virus activity was 4.75 ± 0.02 log10 ID50/mL. The virus neutralization test showed 100% seroconversion by day 9 post-infection and maximum antibody titers (1:32) by day 21. ELISA confirmed that there was a strong immune response (>90% seropositivity). PCR detected viral DNA by day 5 post-infection in most tissues. Necropsy revealed typical pathological sheeppox lesions in the lungs, spleen, lymph nodes, and skin. Histopathological analysis demonstrated acute-stage features including massive cellular infiltration, vasculitis, edema, and pox lesions.ConclusionThe findings confirm previously known characteristics of SPPV and provide new insights into the molecular and pathogenic properties of the “Sheeppox/KZ/Targap/2024” isolate.